2016
DOI: 10.1002/anie.201608119
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Nuclear Polarization Provides New Insights into Chromophore Structure in Phytochrome Photoreceptors

Abstract: Phytochromes are red/far-red photochromic photoreceptors acting as master regulators of development in higher plants, thereby controlling transcription of about 20 % of their genes. Light-induced isomerization of the bilin chromophore leads to large rearrangements in protein structure, whereby the role of protonation dynamics and charge distribution is of particular interest. To help unravel the inherent mechanisms, we present two-dimensional dynamic nuclear polarization (DNP) enhanced solid-state magic-angle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…The experimental δ N values were closely matched by those computed using a QM/MM approach ( δ N21-N24 = 165.3, 140.7, 154.1, and 138.0 ppm, respectively; see Supplementary Table S3 ). It should also be noted that the recent 15 N DNP enhanced MAS NMR characterization of the Pr state in Cph1 finalized the assignment of the Pr resonances ( Stöppler et al, 2016 ), in which the previous tentative assignments of N22 and N23 ( Rohmer et al, 2008 ) were interchanged. This thus forms a solid basis on calculating the state-induced δ N changes of the chromophore in oat phyA3 (see below).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The experimental δ N values were closely matched by those computed using a QM/MM approach ( δ N21-N24 = 165.3, 140.7, 154.1, and 138.0 ppm, respectively; see Supplementary Table S3 ). It should also be noted that the recent 15 N DNP enhanced MAS NMR characterization of the Pr state in Cph1 finalized the assignment of the Pr resonances ( Stöppler et al, 2016 ), in which the previous tentative assignments of N22 and N23 ( Rohmer et al, 2008 ) were interchanged. This thus forms a solid basis on calculating the state-induced δ N changes of the chromophore in oat phyA3 (see below).…”
Section: Resultsmentioning
confidence: 97%
“…We have proposed that the distinct δ N difference between these inner ring nitrogens arises from the asymmetry of the strong hydrogen-bonding interactions with the nearby carbonyl backbone of D272 (D207 in Cph1) and the pyrrole water ( Rohmer et al, 2010 ). Recent DNP-enhanced MAS NMR studies on Cph1 in Pr have suggested that the positive charge carried by the tetrapyrrole system is mainly localized at ring B and thus would account for a downfield shift of N22 relative to that of N23 ( Stöppler et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stabilizing role of the tongue was further probed by site-directed mutations of amino acids comprising three highly conserved tongue motifs. For these NMR investigations on all2699g1 and all2699g1-2 proteins, we used the PSM of the canonical cyanobacterial phytochrome Cph1 (Cph1Δ2) as a reference for the NMR analysis [28,29,30,31,32,33] (see alignment of the sequences in Figure S1). NMR data provided information on the chromophore geometry, flexibility of the GAF1-bound chromophore and its interactions with nearby amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, classical MD simulations were performed by several groups [25,26,27,28]. In addition, Mroginski and coworkers also employed QM/MM simulations [29,30,31] and some recent publications based on this approach can be found in references [32,33,34,35,36,37]. Recently a QM/MM approach was also applied to investigate the covalent binding of the biliverdin (BV) chromophore to phytochrome domains [38] in the NIR FP miRFP670, which was also investigated experimentally [39,40,41].…”
Section: Introductionmentioning
confidence: 99%